A teoria de Rensis Likert e o perfil organizacional da Universidade do Amazonas - Costa, Rosa do Espirito Santo (1977)
This research h.e as an objective to examine the convenience and adaptation of Rensis Likert Theory to a University - in this case theUniversity of Amazonas - and the identification of its organizational styles through the application of his tecniques for the organizational variables related to the human behaviour, the construction of profiles, the examination of its concentTation into Likert four Management Sistems and the comparison with Likert Sistem 4. Thêresults, not only demonstrated the convenience of the application of this medel, as well as permited to evaluate its adaptation to the study of University organizational profiles and the identification of their administrative styles and forms of human organization.